Recent Progress in Solar-Induced Direct Biomass-to-Electricity Hybrid Fuel Cell Using Microalgae as Feedstocks - Peng, Kun-Tao; Wang, Xiang; Peng, Gong; Yu, Lin; Li, Hong-Ye (Frontiers in Bioengineering and Biotechnology, 2021)
Microalgae, as potential biodiesel feedstocks, have been widely reported to accumulate oil via genetic engineering techniques or environmental stress regulation. Recently, the utilization of fuel cell technology to convert biomass into electricity has attracted much more attention due to its high efficiency, low pollution, low noise by microalgae as feedstocks. Normally, platinum and analogous noble metals as catalysts have been already demonstrated although they still exist lots of shortcomings. This mini review presents an overview of various fuel cell technologies with phosphomolybdic acid as catalysts for sustainable energy by using microalgae. Trends from literatures demonstrate that algal-based fuel cells could efficiently generate electricity, and concurrently produce high value-added products. This critical review can provide guiding suggestions for future study of algal-based energy conversion by fuel cell techniques.